Cultural Discourse Statement as Teacher Belief in Intercultural Classes at Universities in Indonesia - Muhammad Aulia (AL-ISHLAH: Jurnal Pendidikan, 2022)
The present study analyses teacher narratives related to teacher belief toward intercultural EFL pedagogy. It aims to investigate cultural discourse statement by university teachers indicating teacher belief about culture. The gap between what the demand for EFL teaching and teacher belief is still understudies, which results in varied interpretations on how an intercultural classroom teaching should be managed. The qualitative design involved 6 university teachers from 3 different universities in Indonesia, representing the west, the central, and the east parts of the Indonesian archipelago. The data were obtained by two different sessions of interviews on each participant. The data were transcribed and transformed into text and analyzed by using discourse analysis with N-VIVO Software. The present study adopted narrative studies, focusing on teacher education and intercultural education. The results of the study revealed that the university teachers have shown their critical awareness towards the interaction between language teaching, culture, and sociocultural relations. They are critically aware of the complexity of culture. And finally, they have critical awareness of interrelated discourse building on identity, power, and other ideological aspects influencing their own teaching context. This study illuminates that cultural belief is one of the most important factors shaping the intercultural teaching and learning activities at university level. The present study needs to be replicated to gain broader outlook of intercultural EFL pedagogy in Indonesia. Future research needs to focus on how personal experiences including formal education can re-build teacher belief that elevates intercultural communicative competence of teacher.